Gowanus : Brooklyn's curious canal - Alexiou, Joseph (New York University Press, 2015)
For more than 150 years, Brooklyn's Gowanus Canal has been called a cesspool, an industrial dumping ground, and a blemish on the face of the populous borough-as well as one of the most important waterways in the history of New York harbor. Yet its true origins, man-made character, and importance to the city have been largely forgotten. Now, New York writer and guide Joseph Alexiou explores how the Gowanus creek-a naturally-occurring tidal estuary that served as a conduit for transport and industry during the colonial era-came to play an outsized role in the story of America's greatest city. F.